MANAGEMEN MUTU TERPADU BERBASIS KINERJA - Nur Setyaningrum (Fakultas Keguruan dan Ilmu Pendidikan Universitas Nahdatul Ulama Indonesia, 2022)
Performance-based management is more directed to work processes, management, development and related rewards. Where the ability, motivation, and opportunities interact with each other. Islamic educational institutions, especially Quran Education Parks are growing from year to year, but in the process of their managing, they are still limited to